A Smart Storage System and Non-Invasive Technique for Spoilage Detection - Parameswari, C.; Rathnamala, S.; Banu, R. Aasifa; Vinothini, V. (Journal of ISMAC, 2023)
Fresh vegetables are widely recognized as a vital source of essential nutrients for a healthy diet, including vegetable sprouts which are consumed globally for their high nutritional value. Only high-quality fruits and vegetables are preferred by those who are health-conscious. Consequently, it is crucial to check the quality of fruits and vegetables. However, consuming raw vegetables poses a significant risk of transmitting intestinal parasites. With a growing awareness of quality in the food and health industry, there is an increasing need for research on defined quality production, preservation during marketing, and evaluation of quality parameters. By addressing these concerns, this proposed non-invasive system presents a promising technique for detecting the quality of stored fruits and vegetables. The suggested system can help ensure the availability of safe and nutritious produce for consumers, thereby contributing to the improvement of public health.
Keywords: IoT; MQ-4 and MQ-135 sensors; Quality detection; Hyper spectral; Freshness of fruits and vegetables